An Fe-MOF nanosheet array with superior activity towards the alkaline oxygen evolution reaction. Issue 6 (26th April 2018) - Zhang, Xiaoxue; Liu, Qin; Shi, Xifeng; Asiri, Abdullah M.; Sun, Xuping
Abstract : Fe-MOF/NF shows superior electrocatalytic performance towards the OER in 1.0 M KOH with a low overpotential of 240 mV at 50 mA cm −2 . Abstract : It is highly desired to develop high-performance non-noble-metal electrocatalysts for the oxygen evolution reaction (OER) in alkaline solutions. In this communication, we report the hydrothermal synthesis of an Fe-MOF nanosheet array on nickel foam (Fe-MOF/NF) using aqueous Fe 3+ and terephthalic acid as precursors. Such an Fe-MOF/NF shows superior electrocatalytic performance towards the OER in 1.0 M KOH with a low overpotential of 240 mV at 50 mA cm −2 and a small Tafel slope of 72 mV dec −1 . Notably, this catalyst also exhibits high long-term electrochemical durability to maintain its activity for at least 30 h. Moreover, this catalyst electrode achieves a high turnover frequency of 0.74 mol O2 per s at an overpotential of 300 mV.